Effect of Pilates exercise on spinal stabilization in sedentary subjects with subacute non-specific low back pain - Benjamaporn Hancharoenkul (Journal of Associated Medical Sciences, 2017)
Background: Modern lifestyle in both young and older people is increasingly sedentary with less demand for physical activity and inadequate active exercise. Fewer bodily movements and static posture, mainly sitting, results in a prolonged back muscle contraction which is a cause of back pain.